THERMODYNAMIC MODEL FOR SOLID IRON IN AQUEOUS SOLUTIONS - Nascimento, L.; Agostinho L., C. L.; Cavalcanti F., B. (Revista Colombiana de Materiales, 2012)
Solid iron can be observed at environmental conditions and also as metallic component of quasicrystalline alloys. Its behavior in aqueous solution is analyzed from some particular thermochemical relationships. The model utilizes free Gibbs energy to obtain pH and p parameters which are related to iron redox reactions. The solid iron system, defined as Fe(s): Fe2+ - Fe3+ - Fe2O3 (hematite) – Fe3O4 (magnetite), was modelled by considering a low molar concentration and environmental temperature. In order to obtain p values, equations relating Gibbs standard free energy and equilibrium constants were applied. A stability diagram such as p x pH was chosen to depict these thermochemical relationships. Thus, straight line dp/dpH slopes were obtained for each process step of the solid iron system. In systems relating solid iron to iron species Fe2+ and Fe3+ the slopes are equal to zero; i.e., a horizontal line shows the iron species dominance in some specific pH range. The negative values obtained show the pH dependence of the iron species investigated. In natural water environment, it is possible to distinguish hematite formation from magnetite formation. However in quasicrystalline AlCuFe alloys the last iron species formed is hematite which ion pairs to copper. Due to the strong pH dependence, it is necessary to measure pH in both environmental condition and quasicrystalline phases formation. Considering that the temperature adopted was 25°C, the results are valid only for this temperature.